Perbandingan iskemik dan hemoragik terhadap prognosis dan pemulihan pasca stroke: Literatur review - Bakri, Zarah Asvirah; Kaelan, Cahyono; Muchsin, Achmad Harun (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2026)
Background: According to the World Health Organization (WHO), stroke is a disturbance in brain function with clinical signs that last more than 24 hours or can lead to death. Stroke is divided into ischemic and hemorrhagic strokes, which have different pathophysiological mechanisms, prognoses, and functional outcomes. Rehabilitation interventions, particularly physical therapy, are the primary approach to improving motor function recovery after stroke. Purpose: To determine the differences in prognosis and recovery between ischemic and hemorrhagic strokes. Method: This study is a systematic literature review that discusses prognosis and recovery after stroke by comparing ischemic and hemorrhagic strokes. Twenty journals were analyzed and synthesized. Results: Prognosis and recovery after stroke are influenced by stroke type, initial severity, and the quality and intensity of rehabilitation. Ischemic strokes generally have a better prognosis than hemorrhagic strokes, which tend to have higher mortality and disability rates. However, intensive rehabilitation interventions, including specific therapies such as mirror therapy, can result in significant functional recovery in both types of stroke. Conclusion: An individualized and comprehensive rehabilitation approach is essential to maximize functional outcomes. Early prognostic predictions should be used cautiously, and intervention strategies targeting cerebral edema and blood-brain barrier dysfunction have the potential to support long-term outcomes. Keywords: Hemorrhagic; Ischemic; Post-Stroke; Prognosis; Recovery. Pendahuluan: Stroke menurut World Health Organization (WHO) merupakan gangguan fungsi otak dengan tanda klinis yang berlangsung lebih dari 24 jam atau dapat menyebabkan kematian. Stroke dibedakan menjadi stroke iskemik dan hemoragik yang memiliki mekanisme patofisiologi, prognosis, serta luaran fungsional yang berbeda. Intervensi rehabilitasi, terutama terapi fisik, menjadi pendekatan utama untuk meningkatkan pemulihan fungsi motorik pasca-stroke. Tujuan: Untuk mengetahui perbedaan prognosis dan pemulihan stroke iskemik dan hemoragik pasca-stroke. Metode: Penelitian ini merupakan studi kepustakaan dengan pendekatan systematic literature review yang membahas prognosis dan pemulihan pasca-stroke melalui perbandingan stroke iskemik dan hemoragik. Sebanyak 20 jurnal dianalisis dan disintesis. Hasil: Prognosis dan pemulihan pasca-stroke dipengaruhi oleh tipe stroke, tingkat keparahan awal, serta kualitas dan intensitas rehabilitasi. Stroke iskemik umumnya memiliki prognosis yang lebih baik dibandingkan stroke hemoragik yang cenderung menunjukkan angka mortalitas dan disabilitas lebih tinggi. Namun, intervensi rehabilitasi yang intensif termasuk terapi spesifik seperti mirror therapy dapat menghasilkan pemulihan fungsional yang bermakna pada kedua tipe stroke. Simpulan: Pendekatan rehabilitasi yang individual dan komprehensif sangat penting untuk memaksimalkan luaran fungsional. Prediksi prognosis awal perlu digunakan secara hati-hati, dan strategi intervensi yang menargetkan edema serebral serta disfungsi blood–brain barrier berpotensi mendukung outcome jangka panjang. Kata Kunci: Hemoragik; Iskemik; Pasca-Stroke; Pemulihan; Prognosis.